Nurses' knowledge and competencies for preceptorship in the basic health unit - Francisco Das Chagas Ferreira; Fernanda de Carvalho Dantas; Geilsa Soraia Cavalcanti Valente
ABSTRACT Objective: to describe the actions performed by nurses in the preceptorship of students in the Basic Health Unit (Portuguese acronym: UBS); to identify the knowledge of nurses and competencies they need to acquire or develop in order to act in the preceptorship of students in the UBS; to discuss the implications of the pedagogical practice of preceptor nurses in their own continuing education. Method: qualitative, descriptive and exploratory nature. Scenario: A UBS. Participants: six preceptor nurses. Data collection: semi-structured interview. Results: Bardin's content analysis was used. Emerging categories: Approaching the concept of preceptor and the teaching role; The fragile institutional recognition of UBS as a field of internship and the offer of knowledge of preceptors: overcoming difficulties; Preceptor nurses' performance in face of dynamics of facts arising and shaping the reality in a UBS; Opportunities and limitations of the pedagogical practice implying on continuing education. Conclusion: it is necessary to discuss and rethink the strategies of interest of preceptors and develop their competencies.